Pauses in Student Group Presentations: UM-SpEAKs - Farahdiba, Tia; Basthomi, Yazid; Prayogo, Johannes A.; Hidayati, Maria; Yannuar, Nurenzia; Suharyad; Ishak, Cita Nuary; P.R.R, Dyah Triajeng (International Journal of Psychosocial Rehabilitation, 2020)
— This study aimed to analyze pauses by male and female students in group presentations. A qualitative study, this project focuses on developing better understanding of pauses by students in classroom group presentation. Two kinds of data were used in this study: (1) UM-SpEAKs (Universitas Negeri Malang Spoken English in Academic Kontexts) corpus and (2) interview data. The analysis was focused on the types and reason(s) for the pauses. The results show that there are different number of silent and filled pauses between male and female students in group presentations. It was found that the most common type of pauses that are made by male and female students is silent pauses. Nervousness or anxiety is the main reason for the occurrence of the pauses in group presentations.